2023
DOI: 10.1002/aenm.202301219
|View full text |Cite
|
Sign up to set email alerts
|

Designed Redox‐Electrolyte Strategy Boosted with Electrode Engineering for High‐Performance Ti3C2Tx MXene‐Based Supercapacitors

Abstract: Ti3C2Tx MXene has shown remarkable potential for supercapacitors. However, its limited capacitance restrains the energy density. Here, a designed redox‐electrolyte strategy boosted with electrode engineering for Ti3C2Tx MXene is demonstrated, by which a record‐high specific capacitance of 788.4 F g−1 at 2 mV s−1 is achieved, accompanied by good rate capability and highly improved cyclic stability compared with the pristine MXene electrode. For the first time, redox additives with redox potentials falling in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…This favorable electrochemical performance originates from the enhanced electron/mass transfer process, which can be traced back to the formation of a ferricyanide anion-philic interface after B incorporation. Benefiting from the constructed ferricyanide anion-philic interface, the capacitance achieved by PC-3 in our study surpasses that of other reported carbon-based electrodes for R-SCs (Figure f). , Benefiting from the simultaneous promotion of mass/charge transfer, the asymmetric supercapacitor assembled with PC-3 can achieve excellent stability, maintaining capacitance retention of 98% even after undergoing 10,000 charge cycles (Figure S11 and Table S1), proving the potential of developed porous carbon which contains a high percentage of B species especially BC 2 O and BCO 2 units in practical energy storage applications.…”
Section: Resultsmentioning
confidence: 55%
“…This favorable electrochemical performance originates from the enhanced electron/mass transfer process, which can be traced back to the formation of a ferricyanide anion-philic interface after B incorporation. Benefiting from the constructed ferricyanide anion-philic interface, the capacitance achieved by PC-3 in our study surpasses that of other reported carbon-based electrodes for R-SCs (Figure f). , Benefiting from the simultaneous promotion of mass/charge transfer, the asymmetric supercapacitor assembled with PC-3 can achieve excellent stability, maintaining capacitance retention of 98% even after undergoing 10,000 charge cycles (Figure S11 and Table S1), proving the potential of developed porous carbon which contains a high percentage of B species especially BC 2 O and BCO 2 units in practical energy storage applications.…”
Section: Resultsmentioning
confidence: 55%
“…[31][32][33] In the MXene family, Ti 3 C 2 T x stands out for its high conductivity, excellent specific capacitance and abundant ion transmission channels. [34][35][36] Nevertheless, stacking of the Ti 3 C 2 T x layers may occur due to the van der Waals interactions, which can seriously limit the specific surface area and pore distribution and hence the electrochemical performance. [37][38][39] To mitigate this issue, aniline (ANI) monomers can be chemisorbed onto the surface of the Ti 3 C 2 T x nanosheets and in situ polymerized to prepare Ti 3 C 2 T x @PANI heterostructures.…”
Section: Introductionmentioning
confidence: 99%